2021
DOI: 10.3390/ani11020245
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of New Haplotype of Genus Sarcocystis in Seabirds from Magdalena Island, Southern Chile

Abstract: Evidence of sarcocystid infection was investigated in samples of 16 penguins (Spheniscus. magellanicus), four Dominican gulls (Larus dominicanus) and two Chilean skuas (Stercorarius chilensis) found in Madalenas Islands, Chile, in 2017. Samples of skeletal muscle, cardiac muscle and brain from all birds were screened by a pan-sarcocystid nested-PCR targeting a short fragment of the gene encoding the small ribosomal unit (nPCR-18Sa). The only two positive samples by nPCR-18Sa, both from skuas, were tested by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…studies infecting avian species (Gjerde et al, 2018;Prakas et al, 2023). This is because the ITS1 gene has a more variable locus owing to the higher amount of indels such as insertions and/or deletions than the 18S rRNA gene, hence containing more important phylogenetic data to differentiate species within the genus (Acosta et al, 2021;Prakas et al, 2023). Sarcocystis wenzeli infection in this study was confirmed by ITS1 gene sequencing and phylogenetic trees; the analyses revealed six variants clustered with those from China and Brazil.…”
Section: Discussionsupporting
confidence: 59%
“…studies infecting avian species (Gjerde et al, 2018;Prakas et al, 2023). This is because the ITS1 gene has a more variable locus owing to the higher amount of indels such as insertions and/or deletions than the 18S rRNA gene, hence containing more important phylogenetic data to differentiate species within the genus (Acosta et al, 2021;Prakas et al, 2023). Sarcocystis wenzeli infection in this study was confirmed by ITS1 gene sequencing and phylogenetic trees; the analyses revealed six variants clustered with those from China and Brazil.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, Sarcocystis sp. in the Chilean skua ( Stercorarius chilensis [Bonaparte, 1857]) from Chile (see Acosta et al, 2021 ; Prakas et al, 2021 ) also formed a sister branch. Our phylogenetic analysis showed similar branching, so it is difficult to state whether these sequences belong to the same species, until more samples are molecularly obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac apex (approximately 10~20 g) was added to 150 ml of tissue lysate, mixed until liquid using a mixer, and then dissolved with Proteinase K at 56 °C overnight. The next morning, DNA was extracted using Qiagen's DNeasy Blood & Tissue kit and nested-PCR targeting the B1 gene of T. gondii was performed 62 . The oligonucleotides corresponding to the B1 gene were as follows: B1-T1: AGCGTCTCTCTT CAAGCAGCGTA, B1-T2: TCCGCAGCGACTTCTATCTCTCTGT, B1-T3: TGGGAATGAAAGAGACGCTAATGTG, B1-T4: TTAAAGCGTTCGTGGT CAACTATCG.…”
Section: Bioassay In Micementioning
confidence: 99%